2023
DOI: 10.3389/fcvm.2023.1143886
|View full text |Cite
|
Sign up to set email alerts
|

Use of left atrial appendage as an autologous tissue source for epicardial micrograft transplantation during LVAD implantation

Abstract: We report here the first clinical use of the left atrial appendage (LAA) for epicardial micrograft transplantation during left ventricular assist device (LVAD) implantation. Previously, a sample from the right atrial appendage (RAA) has been available for processing and administering micrograft therapy in cardiac surgery. Both LAA and RAA are rich sources of various types of myocardial cells and are capable of providing both paracrine and cellular support to the failing myocardium. The surgical approach of LAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Subsequent preliminary clinical trials confirmed the feasibility and safety of atrial appendage micrografts in cardiac surgery in patients with stable coronary artery disease or chronic HF. 73 However, because of the unique challenges in harvesting atrial appendage micrografts and the time required for intraoperative preparation, its application in acute MI or HF cases is limited. Future exploration of allogeneic sources as alternatives could broaden their applicability; however, issues related to donor availability and immunogenicity remain significant challenges.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Subsequent preliminary clinical trials confirmed the feasibility and safety of atrial appendage micrografts in cardiac surgery in patients with stable coronary artery disease or chronic HF. 73 However, because of the unique challenges in harvesting atrial appendage micrografts and the time required for intraoperative preparation, its application in acute MI or HF cases is limited. Future exploration of allogeneic sources as alternatives could broaden their applicability; however, issues related to donor availability and immunogenicity remain significant challenges.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%